2011
DOI: 10.1007/s10745-011-9421-z
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Location Analysis of the Impact of Household Socioeconomic Status on Participation in Urban and Peri-Urban Agriculture in West Africa

Abstract: This study explores the relation between household socioeconomic status (SES) and participation in urban and periurban agriculture (UPA) in three West African cities. We used a structured questionnaire to survey 700 randomly selected households: 250 in Kano, Nigeria, 250 in Bobo Dioulasso, Burkina Faso, and 200 in Sikasso, Mali. Multiple correspondence analysis was applied on household asset variables to create an index of assets which was used as a proxy for household SES. The results showed no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 64 publications
2
26
1
3
Order By: Relevance
“…Several authors have used MCA as a weighting method for the construction of a composite index (Canuel et al 2014;Charreire et al 2010;Cortinovis et al 1993;Dossa et al 2011;Howe et al 2008). MCA is a data reduction procedure for categorical variables (nominal or ordinal) as much as Principal Components Analysis is for quantitative variables (Greenacre 2007).…”
Section: Building the Indexmentioning
confidence: 99%
“…Several authors have used MCA as a weighting method for the construction of a composite index (Canuel et al 2014;Charreire et al 2010;Cortinovis et al 1993;Dossa et al 2011;Howe et al 2008). MCA is a data reduction procedure for categorical variables (nominal or ordinal) as much as Principal Components Analysis is for quantitative variables (Greenacre 2007).…”
Section: Building the Indexmentioning
confidence: 99%
“…The difference in land availability between Jessore and Tongi may affect these UPA characteristics. Dossa et al (2011) revealed a negative relationship between population density and the prevalence of UPA in African urban cities. In an urban city with a high population density, such as Tongi, the nutritional and/or economic benefits of engaging in UPA appear to be confined to a small proportion of urban dwellers.…”
Section: Resultsmentioning
confidence: 97%
“…In Jessore, the predicted probability of engaging in UPA is 33.8% for a household with the number of family members equal to the mean minus the standard deviation ( ), 41.7% at the mean ( ), and 50.1% at the mean plus the standard deviation ( ). As pointed out by Dossa et al (2011) andMaxwell (1995) when examining the case of urban cities in Africa, the more members there are in a family, the more likely a family is to engage in urban agriculture in Jessore. The predicted probability for a household with more than one child under five years old to engage in UPA is 35.5%, which is 12.4% lower than that for a household without any children under five, indicating that having a young child under five is a deterrent for engaging in UPA in Jessore.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations